Research on Impact of Rain Infiltration on the Stability of Expansive Soil Slope - CEN Weijun; WANG Yongli; SHI Conghao; YUAN Lina (Renmin Zhujiang)
Expansive soil is a kind of special geotechnical material that expands with waterincreasing and shrinks with water loosing, and water has a significant effect on its mechanicalproperties. Taking an expansive soil slope in Henan province of the middle route of South-to-NorthWater Diversion Project as an example, considering the double coupling effect between seepagefield and stress field, this paper studies the influence of rainfall infiltration on the anti-sliding stability of expansive soil slope by finite element strength reduction method. Thecalculation shows that with the increase of rainfall intensity and duration, the safety factor ofanti-sliding stability of slope decreases. Upon considering the influence of rainfall infiltrationon the shear strength of expansive soil, the safety factor of slope decreases significantly.